Tetrahedral framework nucleic acids as an advanced drug delivery system for oligonucleotide drugs - Liu, Yuhao; Liu, Zhiqiang; Cui, Weitong; Li, Yanjing; Qin, Xin; Zhang, Mei; Lin, Yunfeng (APL materials, 2020)
Nucleic acid therapy has played a promising role in the treatment of many diseases, such as cancer, infections, immune diseases, and neurodegenerative diseases. However, its application is still limited mainly because of poor cell-entry performance and low resistance to in vivo degradation. Tetrahedral framework nucleic acids (tFNAs) have shown potential in delivering low-molecular-weight drugs owing to their stability, biocompatibility, cell-entry performance, and flexible drug-loading ability. In particular, tFNAs can successfully deliver oligonucleotide drugs with improved effects and co-deliver oligonucleotide drugs with other drugs for synergistic effects. In this review, the recent progress on tFNA-based delivery of oligonucleotide drugs is outlined by single delivery systems—through sequence extension and complementation, and co-delivery systems—through multiple sequence extension, drug–DNA interactions, and specific binding. Furthermore, the current limitations and future developments of tFNA-based delivery of oligonucleotide drugs are discussed.